The YfcO fimbriae gene enhances adherence and colonization abilities of avian pathogenic Escherichia coli in vivo and in vitro. (November 2016) - Li, Yaxin; Wang, Haojin; Ren, Jianluan; Chen, Ling; Zhuge, Xiangkai; Hu, Lin; Li, Dezhi; Tang, Fang; Dai, Jianjun
Abstract: Chaperone-usher (CU) fimbriae, which are adhesive surface organelles found in many Gram-negative bacteria, mediate tissue tropism through the interaction of fimbrial adhesins with specific receptors expressed on the host cell surface. A CU fimbrial gene yfcO, was identified in avian pathogenic E. coli (APEC) strain DE205B via gene functional analysis. In this study, yfcO was found in 13.41% (11/82) of E. coli strains, including phylogenetic groups A, B1, B2 and D, with the highest percentage in group B2. The expression of yfcO in biofilm forming bacteria was significantly higher (P < 0.05) than that in the planktonic bacteria. A yfcO deletion mutant was constructed, and adherence to DF-1 chicken embryo fibroblast cells was analyzed in vitro . Compared to the wild-type (WT), adherence of the mutant to DF-1 cells was significantly decreased ( P < 0.01). The mutant bacterial loads in the heart, brain and liver were significantly lower ( P < 0.05) than those of the WT strain. Resistance of the mutant to acidic (acetic, pH 4.0, 20 min) and high osmolarity (2.5 M NaCl, 1 h) stress conditions decreased by 51.28% (P < 0.001) and 80.34% ( P < 0.01), respectively. These results suggest that yfcO contributes to APEC virulence through bacterial adherence to host tissues. Highlights: Successfully constructed yfcO gene deletion mutant strains and complementation strains of DE205B. Demonstrated the YfcO fimbriae gene enhances adherence and colonization abilities of avian pathogenic E. coli . Demonstrated the YfcO gene plays a role in resistance to environmental stress of avian pathogenic E. coli .